Research, and nursing care: nurse’s perspective from the university hospital - Mesquita, Ana Maria Ribeiro Cardoso; Andriola, Wagner Bandeira; Vieira, Neiva Francinely Cunha (Rev Rene, 2007)
This research aimed at understanding the relationship between research and assistance from the clinical nurses’ point of view at a Teaching University Hospital. It was a qualitative study accomplished with twenty-two nurses who were interviewed from April to March 2005. The results highlighted that the nurses had recognized the university hospital as a broad field for the activities of research and assistance in search of the improvement of the quality of services rendered to the population and of the professional development of the people. Even though the individual and institutional difficulties are limiting factors, the graduation courses have impelled the nurses to accomplish researches but gaps in the academic formation alert that there are curricular change difficulties and more investment in research and under graduation. Therefore, the accomplishment of researches that result from care is a personal and professional gain but it becomes hostage of individual and institutional interests or of graduate programs being turned into a laborious and demotivating activity which has the need of an institutional policy to change such aspects.